Antidepressant-Like Effect of Bupleurum Paeonia Liujunzi Decoction on Depression Model Mice and its mechanism. Issue 3 (March 2021) - Xing, Zhiyu; Liu, Shengli; Xu, Chang; Xiao, Junke; Liu, Jihong; Li, Li; Gao, Xiaoyao; Wang, Zirui; Zheng, Qingting; He, Yuting; Lv, Shaohui; Gao, Chaopeng; et al.
Abstract: To investigate the behavioral effects and mechanisms of Bupleurum Paeonia Liujunzi Decoction (BPLD) in depression model mice. Twenty male Kunming mice were randomly divided into four groups: blank group, model group, fluoxetine group and Bupleurum Paeonia Liujunzi Decoums combined with reserpine gavage. Fluoxetine group were given fluoxetine treatment at 2mg/kg/d and Bupleurum Paeonia Liujunzi Decoctiction group. Depression model mice were induced by the chronic unpredictable mild stress (Con group were given BPLD treatment at 8g/kg/d. The model group and the blank group were given normal saline once a day. The experiment lasted for 7 days, during which the general state (body weight, hair color, etc.) was recorded and the changes were observed. The serum levels of norepinephrine (NE) and dopamine (DA) were detected by ELISA kit. Compared with the model group, the body weights of the diazepam group and the Chinese medicine group were significantly increased (P<0.01). In addition, it produced the concentrations of NE and DA in the serum were significantly increased (P<0.05) in the two groups. Bupleurum Paeonia Liujunzi Decoction has obvious therapeutic effect on depressed mice, and its mechanism may be related to the increase of NE and DA concentrations.